3D R2* mapping of the placenta during early gestation using free‐breathing multiecho stack‐of‐radial MRI at 3T. Issue 1 (24th August 2018) - Armstrong, Tess; Liu, Dapeng; Martin, Thomas; Masamed, Rinat; Janzen, Carla; Wong, Cass; Chanlaw, Teresa; Devaskar, Sherin U.; Sung, Kyunghyun; Wu, Holden H.
Abstract : Background: Multiecho gradient‐echo Cartesian MRI characterizes placental oxygenation by quantifying R 2 * . Previous research was performed at 1.5T using breath‐held 2D imaging during later gestational age (GA). Purpose: To evaluate the accuracy and repeatability of a free‐breathing (FB) 3D multiecho gradient‐echo stack‐of‐radial technique (radial) for placental R 2 * mapping at 3T and report placental R 2 * during early GA. Study Type: Prospective. Population: Thirty subjects with normal pregnancies and three subjects with ischemic placental disease (IPD) were scanned twice: between 14–18 and 19–23 weeks GA. Field Strength: 3T. Sequence: FB radial. Assessment: Linear correlation (concordance coefficient, ρc ) and Bland–Altman analyses (mean difference, MD) were performed to evaluate radial R 2 * mapping accuracy compared to Cartesian in a phantom. Radial R 2 * mapping repeatability was characterized using the coefficient of repeatability (CR) between back‐to‐back scans. The mean and spatial coefficient of variation (CV) of R 2 * was determined for all subjects, and separately for anterior and posterior placentas, at each GA range. Statistical Tests: ρc was tested for significance. Differences in mean R 2 * and CV were tested using Wilcoxon Signed‐Rank and Rank‐Sum tests. P < 0.05 was considered significant. Z‐scores for the IPD subjects were determined. Results: FB radial demonstrated accurate (ρc ≥0.996; P < 0.001; |MD|<0.2s −1 ) and repeatable (CR<4s −1 ) R 2 * mapping in a phantom, and repeatable (CR≤4.6s −1 ) R 2 * mapping in normal subjects. At 3T, placental R 2 * mean ± standard deviation was 12.9s −1  ± 2.7s −1 for 14–18 and 13.2s −1  ± 1.9s −1 for 19–23 weeks GA. The CV was significantly greater ( P  = 0.043) at 14–18 (0.63 ± 0.12) than 19–23 (0.58 ± 0.13) weeks GA. At 19–23 weeks, the CV was significantly lower ( P < 0.001) for anterior (0.49 ± 0.08) than posterior (0.67 ± 0.11) placentas. One IPD subject had a lower mean R 2 * than normal subjects at both GA ranges (Z<–2). Data Conclusion: FB radial provides accurate and repeatable 3D R 2 * mapping for the entire placenta at 3T during early GA. Level of Evidence : 2 Technical Efficacy : Stage 1 J. Magn. Reson. Imaging 2019;49:291–303.